A Critical Evaluation of The Compatibility Between Traditional And Contemporary Applications of Murabahah Transactions - Olorogun Lukman Ayinde (Aceh International Journal of Social Science, 2012)
Abstract - The present study explores the extent of conceptual resemblance between traditional and contemporary murabahah contracts. In order to assess the discrepancies, qualitative and quantitative content analyses are applied as research methodology. In particular, discrepancies of the conceptual basis of the two contracts are evaluated by content analysis through graphical presentation. The results of this study affirm that the critique raised against contemporary contracts is indeed justified. The comparative analysis of the conceptual differences between traditional and contemporary murabahah contracts leads to the conclusion that the contemporary murabahah contract is in inverse relation to the traditional murabahah contract.